Population of Phosphate Solubilizing Bacteria and Arbuscular Mycorrhizae in the Rhizosphere of Maize and Peanut in Different Cropping Patterns on Dry Land - Ayu Dian Fataya; Widyatmani Sih Dewi; Vita Ratri Cahyani (Nusantara Science and Technology Proceedings, 2023)
Dry land has several limiting factors, namely low organic C, low soil fertility, and limited water caused by very low rainfall. Strategies to increase the productivity of dry land can be done by combining the use of organic matter, cover crops, and intercropping crop systems. The existence of functional microbiota including phosphate solubilizing bacteria (PSB) and arbuscular mycorrhiza (AM) could be used as an indicator to evaluate the status of soil health in agricultural dry land areas. The purpose of this study was to analyze and compare the population density and diversity of PSB and AM in the rhizosphere of maize and peanut in monoculture and intercropping dry lands. A descriptive exploration method was conducted by sampling the rhizosphere soil of maize and peanut in the monoculture and intercropping dry lands to analyze the population density and diversity of PSB and AM spores. Each plot was analyzed in 3 replications. The results showed that the rhizosphere soil of maize in the monoculture dry land had the highest population density and diversity of PSB followed by maize in the intercropping dry land. The rhizosphere soil of maize in the intercropping dry land showed the highest AM spore density and diversity followed by maize in the monoculture dry land. So, this finding indicated that maize plants provide more conducive services in dry land.